The Offertory as Anamnesis toward Ethical Action: Common Worship as a Case Study. (September 2019) - Strout, Shawn
Liturgical scholarship identifies the memorial section of the Eucharistic Prayer as the anamnesis. However, Eucharistic liturgies can contain multiple anamneses. For example, Alexander Schmemann speaks of the anamnetic quality of the Great Entrance in the Byzantine Rite in his book The Eucharist . In Anglican worship, the offertory rite is juxtaposed (à la Gordon Lathrop) with the prayers of penitence, prayers of intercession, and the peace. These juxtapositions produce the type of transformative opportunities Bruce Morrill discusses in his book Anamnesis as Dangerous Memory . In this paper, I examine the offertory rite as found in the Church of England's Common Worship as an example of this juxtaposition. Using Schmemann, Lathrop and Morrill's liturgical theology as foundational, I argue that the offertory rite in Anglican worship is anamnetic and can lead to a transformative encounter with Christ, leading to ethical action.